Syntactically Anomalous Idioms in Croatian - Broz, Vlatko; Zovko Dinković, Irena (2012)
Apart from idioms with a regular syntax, every language has a number of idioms with a structure that deviates from the norm or violates the conventional rules of grammar. Such idioms are also known as extragrammatical (Fillmore et al. 1988:505), ill-formed (Moon 1998:20), syntactically deviant (Taylor 2002:556) or syntactically idiosyncratic (Langlotz 2006:132). Their syntax cannot be analyzed according to predictable syntactic rules because they contain strange uses of word classes, ellipsis or remnants of earlier uses, as for example all of a sudden, six feet under and by and large. Syntactically anomalous idioms are therefore considered non-compositional, i.e. it is not possible to analogize or modify them (Gibbs 2007:704-9). This paper focuses on syntactically anomalous idioms in Croatian comparing their characteristics to those found in English (Moon 1998: 80). In doing so, we primarily aim at proving that their syntactic ill-formedness is proportional to their semantic opacity, which in turn accounts for the way in which speakers understand, use and process them. The usage of 25 frequent Croatian idioms randomly selected from Croatian dictionaries was investigated both in corpora and through questionnaires with native speakers of Croatian. The questionnaires also tested the predictability of context types in which the idioms occur. References Fillmore, Charles J., Kay, P., O’Connor, M. C. (1988). Regularity and idiomaticity in grammatical construction: The case of let alone, in Language, 64: 501–538 Gibbs, Raymond. Idioms and formulaic language. in Geeraerts, D. and Cuyckens, H. (eds.) (2007). The Oxford Handbook of Cognitive Linguistics, Oxford: Oxford University Press Langlotz, Andreas. (2006). Idiomatic Creativity: A Cognitive Linguisic Model of Idiom-Representations and Idiom-Variation in English, Amsterdam and Philadelphia: John Benjamins Publishing Company Moon, Rosamund. (1998). Fixed expressions and Idioms in English, Oxford: Oxford University Press, Calendon Press Taylor, John R. (2002). Cognitive Grammar, Oxford: Oxford University Press: 437-586
Projekt MZOS
ENG